Experimental & Numerical Evaluation of Borehole Thermal Energy Storage Fields - Millar, Chantel (My University, 2025)
The research begins with expanding the scope of the thermal response test (TRT) to include atypical borehole heat exchangers. This first study explores the use of the infinite line source when used to evaluate the temperature response of a TRT on a series of boreholes. This can occur in practical applications in which existing borehole fields need recharacterization when field operation has persisted over multiple years or field modifications have been made. When a TRT is conducted on boreholes arranged in series there can be thermal interactions between the boreholes that will impact the temperature response. The study established that to minimize the effect of thermal interaction, a Fourier number of less than 0.06 is required. The investigation then focuses on thermal performance of a borehole thermal energy storage field (BTES). This study provides an extensive experimental dataset of the operation of a BTES supplemented with a fully 3D numerical model created within COMSOL Multiphysics. The results show that the COMSOL model of the borehole field was able to capture the thermal response of heat injection and extraction cycles to within 4.5% of the experimental results. Next, an investigation into the thermal losses from BTES was conducted. This study included a numerical and experimental examination of temperature, energy, and exergy throughout an entire heat injection and extraction cycle. This study also introduces a novel concept of zonal operation of borehole fields. The new designation of “zones” is introduced as independently controlled (temperature, mass flow rate) concentric areas within the borehole field. The conclusions outlined that operating a zonal BTES, with a lower temperature concentric radial second zone, the quality of the injected heat in the center zone is maintained. The energy efficiency of the two-zone field increased thermal efficiency by nearly 20% compared to the typical series arrangement borehole field.
Keywords: borehole heat exchanger; numerical modelling; thermal response test; experimental dataset; exergy analysis; zonal operation